COMPARATIVE CRYSTAL-STRUCTURE STUDY OF AG-FREE LILLIANITE AND GALENOBISMUTITE FROM VULCANO, AEOLIAN ISLANDS, ITALY - Pinto D.; Garavelli A.; Vurro F.; Balić-Žunić T.; Makovicky E. (My University, 2006)
The crystal structures of natural Ag-free lillianite of fumarolic origin from Vulcano, Aeolian Islands, Italy, Pb2.88 Bi2.12 (S5.67Se0.33) ∑6.00, with a 13.567(1), b 20.655(2), c 4.1216(4) Å, V 1155.0(2) Å3, space group Bbmm, Z = 4, and galenobismutite also from Vulcano, Pb1.00 Bi2.03 (S3.87Se0.11) ∑3.98, with a 11.815(2), b 14.593(2), c 4.0814(6) Å, V 703.7(2) Å3, space group Pnam, Z = 4, were refined from single-crystal X-ray data. The refinements converge to R = 3.40% [for 745 reflections with Fo > 4σ,(Fo)], and R = 2.96% [for 607 reflections with Fo > 4σ(Fo)] fo Ag-free lillianite and galenobismutite, respectively. In Ag-free lillianite, the trigonal prism M3 is occupied only by Pb, whereas both the octahedrally coordinated M1 and M2 sites are mixed (Pb,Bi) positions. The same octahedra incorporate both the surplus of Bi and vacancies (□) created by the substitution 3Pb2+ → 2Bi3+ + □, which allows for the observed deviations from the ideal composition, Pb3Bi2S6. Selenium is preferentially ordered at the six-fold and five-fold coordinated anionic sites, whereas the four-fold coordinated site S3 remains free of Se. The known structural arrangement of galenobismutite was confirmed in this work. The octahedrally coordinated M1gb site was found to be a full Bi position. Some evidence of Pb-Bi disorder has been observed at both the M2gb (Bi-dominated) and M3gb (Pb-dominated) positions. A heterogeneous distribution of Se in the anionic S sites was observed in galenobismutite. Atoms of Se are mainly concentrated at the site S1 and less so in the other anionic sites.
Keywords: AG-FREE LILLIANITE; CRYSTAL STRUCTURE; FUMAROLES; GALENOBISMUTITE; ITALY; VULCANO